Entrepreneurship management of islamic boarding schools - Feri Sandria; Ulil Amri Syafri; Akhmad Alim; Mas’udin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The impact of globalization complicates the situation and emphasizes the importance of the economic aspect in the world of work. The high unemployment rate indicates that graduates of educational institutions are often less competitive due to weak human resources. Human resources are greatly influenced by the quality of education, to provide quality education in addition to human resources as teaching staff must also be supported by adequate facilities and infrastructure, to create a quality educational atmosphere is inseparable from the relatively expensive budget. The cost of education is certainly relatively expensive if all of it is charged to the parents of students, to overcome this educational institution must process to be independent in terms of economy, including by presenting entrepreneurship in educational institutions. To achieve a prosperous life, both providers and recipients of education need to understand the concept of entrepreneurship. The presence of entrepreneurs provides support for the achievement of educational goals. Islamic boarding schools, as Islamic educational institutions, design a curriculum that combines aspects of religion and world knowledge in one unit. A dynamic and intensive educational approach influences the formation of the character of students, including an independent attitude. The potential for student independence is the basis for Islamic boarding schools in developing economic aspects. The principles that need to be considered in developing business units in Islamic boarding schools include: (1) ownership of the business unit by the institution itself, where the leadership does not have the authority to make unilateral decisions regarding financial management; (2) implementing good governance to maintain trust, including reporting and holding regular consultations between leaders regarding the development of the business unit; (3) recruiting workers who are experts in their fields and come from within the institution to ensure effective communication; (4) paying attention to the legal aspects of the business entity to optimize available opportunities; and (5) forming a team of experts, at least involving senior staff, to oversee the development of the business unit.